2017
DOI: 10.1097/tp.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Developing Consensus-Based Priority Outcome Domains for Trials in Kidney Transplantation

Abstract: Background Inconsistencies in outcome reporting and frequent omission of patient-centered outcomes can diminish the value of trials in treatment decision-making. We identified critically important outcome domains in kidney transplantation based on the shared priorities of patients/caregivers and health professionals. Methods In a 3-round Delphi survey, patients/caregivers and health professionals rated the importance of outcome domains for trials in kidney transplantation on a 9-point Likert scale and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…3942 These core outcome sets were developed using an evidence- and consensus-based process (systematic review, focus groups with nominal group technique, stakeholder interviews, an international Delphi Survey, and a consensus workshop) involving more than 1300 patients, caregivers, and health professionals from more than 70 countries in each stream (i.e., hemodialysis, kidney transplantation). 1012,37,38,40,41 The findings from the workshop will inform strategies and pathways for implementing core outcomes, with a focus on trials in nephrology.…”
mentioning
confidence: 99%
“…3942 These core outcome sets were developed using an evidence- and consensus-based process (systematic review, focus groups with nominal group technique, stakeholder interviews, an international Delphi Survey, and a consensus workshop) involving more than 1300 patients, caregivers, and health professionals from more than 70 countries in each stream (i.e., hemodialysis, kidney transplantation). 1012,37,38,40,41 The findings from the workshop will inform strategies and pathways for implementing core outcomes, with a focus on trials in nephrology.…”
mentioning
confidence: 99%
“…The prioritization of mortality and graft function is consistent with the findings of another Delphi survey of patients/caregivers and health care providers on priority outcomes in kidney transplantation trials. 24 We extend these findings by identifying exercise, specifically pre- and postoperative rehabilitation, as a therapeutic strategy of interest to modify these outcomes. So far, studies have demonstrated that pretransplant rehabilitation is a potential intervention for increasing physical activity preoperatively and may also decrease post-transplant length of stay.…”
Section: Discussionmentioning
confidence: 82%
“…Sautenet et al reported consensus outcomes for kidney transplantation among patients, caregivers and HCPs. 97 They found that patients/caregivers from certain countries ranked ‘depression’ or ‘cognition’ as less important and that ‘skin cancer’ received greater prioritisation in countries with public campaigns for prevention. Since none of the aforementioned outcomes were ranked in the ‘top eight’ of either patients or HCPs, these differences did not affect the final COS. Van Rijssen et al 73 reported consensus PROs for pancreatic cancer among European, North American and Asian participants.…”
Section: Resultsmentioning
confidence: 99%
“…A minority of studies (4%, n=4) analysed, or stated an intention to analyse, the Delphi survey responses by participants' geographical location, either by country 54 97 or continent. 73 Some differences in outcome prioritisation were minor, not affecting the final COS. 54 97 Park et al presented results from round 1 of their Delphi survey on patient-reported outcomes (PROs) for adult myositis. 54 They found that, unlike participants from the USA and South Korea, Swedish participants rated 'impact on household activity' less favourably, although this outcome was still retained for the second Delphi round.…”
Section: International Status Of Participants and Effect On Outcome Pmentioning
confidence: 99%